Penerapan Prinsip Andragogik oleh Tutor pada Pelatihan Make Up Wardah Cosmetic di Kota Padang - Musarah Musarah; Jamaris Jamaris; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is based on the high interest and participation of the participants of make up training because the tutor applies the principles of andragogik on Wardah Cosmetic training process in Padang City. So this study aims to illustrate the application of principles andragogik by Tutor seen from the performance, environmental management of learning environment, and implementation of learning evaluation. Type This research is a quantitative descriptive with the population is the trainer participants to be sampled by use cluster random sampling technique. Data collection tool used is a questionnaire with data analysis of percentage calculations. The result of the research shows that in general the Application of Andragogic Principle by tutor in Wardah Cosmetic make up training in Padang City has been running well, viewed from the performance of tutor, the management of learning environment atmosphere, the implementation of learning evaluation.